The Effect of Widyaiswara's Performance on the Condition of Participants in Education and Training at the West Sumatra Province Human Resources Development Agency - Nadia Wati; Warma Novita; Pioni Marta Sari; Rindiani Ningsih (Universitas Negeri Padang, 2020)
The background of this article has to make the high quality of humans resources can improving the quality of the nation towards prosperity. While the low grade of a country citizens can bring quality by a nation towards a nation that is difficult to progress and difficult to prosper. From this program, we will expand citizen skills with educations and training or better known as (Diklat). Education and training is a place for institutions that dedicate their existence to education that aims to improve and develop Human Resources (HR) in an institution or agency. To carry out education and training in the human resource development body, it takes educators called widyaiswara.Keywords: Human Resource, Training, Widyaiswara